Assessment of gamma radiation induced genetic variability in Jatropha curcas using RAPD and DAMD markers - BHUMI, SHAH; GAUTAM, SARIPALLI; AKSHAY, ROLA; FENIL, PATEL; FOUGAT, R S (The Indian Journal of Agricultural Sciences, 2026)
Gamma radiation induced variability among the Jatropha accessions was assessed using morphological and molecularmarkers (RAPD and DAMD) . Various treatments (0, 1, 3, 5, 10, 15, 20, 25, 50 Kr) of gamma radiation doses were givento Jatropha curcas L. genotype Urulikanchan and a total of 32 mutants and 1 control were included in the present studyon the basis of various doses. Some variation in germination% was observed with different doses whereas characters likeheight, girth and canopy diameter showed non significant variation. The 15 RAPD and 4 DAMD primers were used whichproduced polymorphism percentage of 74.23% and 73.68%. PIC values of the markers ranged from 0.732 to 0.904 (RAPD)and 0.765 to 0.868 (DAMD) respectively. RAPD primers OPA 18, OPB 10, OPH 12, OPF 4 and OPI 5 produced bandswhich were specific to some mutants and hence helpful in identifying those mutants. Similarly, DAMD primers, HBV andHRV also produced specific banding profiles. Comparison studies showed very less correlation between the two markersas deduced from the r value (r=0.44). Both the markers proved efficient for polymorphism detection in gamma radiation treated J.curcas mutant.